Clinical seizures and unfavorable brain MRI patterns in neonates with hypoxic ischemic encephalopathy. Issue 12 (26th March 2021) - Lin, Yen-Kuang; Hwang-Bo, Seok; Seo, Yu-Mi; Youn, Young-Ah
Abstract : Abstract: The aim was to examine whether clinical seizures and amplitude-integrated electroencephalogram (aEEG) patterns in infants with hypoxic ischemic encephalopathy (HIE) can predict the extent of brain injury on magnetic resonance images (MRI) and the long-term neurodevelopmental outcomes at 18∼24 months of age. HIE infants who underwent therapeutic hypothermia (TH) between June 2014 and March 2017 were included in this study. Infants with clinical seizure were analyzed for aEEG patterns and the extent of brain injury on MRI findings. Clinical seizure, aEEG, and brain MRI were assessed and compared with neurodevelopmental outcomes at 18∼24 months of age. Among the 97 HIE infants enrolled in this study with brain MRI scans, 78 (73.1%) TH-treated HIE infants exhibited clinical seizures. More abnormalities on a EEGs and more significant use of first and second antiepileptic drugs (AEDs) were significantly higher in the clinical-seizure group with longer hospitalized days. At a corrected 18 to 24 months of age, HIE infants in the clinical-seizure group with more extension of injury lesions on diffusion-weighted MRI scans exhibited significantly more delayed neurodevelopment. A risk factor analysis indicated that male infants who stayed in the hospital for more than 11 days were at a higher risk of having clinical seizures. The lesion size in MRI greater than 37 pixels was a risk factor with an 81.8% accuracy. Seizures in HIE infants may predict abnormal brain MRI scans and abnormal neurodevelopment at 18 to 24 months of age.